2005
DOI: 10.1021/es051689g
|View full text |Cite
|
Sign up to set email alerts
|

Is Cumulative Fossil Energy Demand a Useful Indicator for the Environmental Performance of Products?

Abstract: The appropriateness of the fossil Cumulative Energy Demand (CED) as an indicator for the environmental performance of products and processes is explored with a regression analysis between the environmental life-cycle impacts and fossil CEDs of 1218 products, divided into the product categories "energy production", "material production", "transport", and "waste treatment". Our results show that, for all product groups but waste treatment, the fossil CED correlates well with most impact categories, such as globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
229
0
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(241 citation statements)
references
References 36 publications
8
229
0
4
Order By: Relevance
“…CED is expressed in mega joules (MJ). In addition, Huijbregts et al (2005) found that CED correlates well with most environmental life cycle impact categories and can be considered an appropriate proxy indicator for environmental performance.…”
Section: Eutrophication Potential Eutrophication Potential (Ep) Ismentioning
confidence: 95%
“…CED is expressed in mega joules (MJ). In addition, Huijbregts et al (2005) found that CED correlates well with most environmental life cycle impact categories and can be considered an appropriate proxy indicator for environmental performance.…”
Section: Eutrophication Potential Eutrophication Potential (Ep) Ismentioning
confidence: 95%
“…NREU represents a straightforward and practical approach because many environmental impacts are related to energy use (13). NREU encompasses fossil and nuclear energy and was expressed as higher heating value (HHV), also called the gross calorific value.…”
Section: Environmental Indicatorsmentioning
confidence: 99%
“…From the beginning, this measure of "cumulative energy demand (CED)" has actually been considered the "most important aggregated result of the inventory used for compari-sons of product-related systems," as stipulated by Klöpffer in an editorial in the International Journal of Life Cycle Assessment [20]. According to the research by Huijbregts et al, "fossil CED correlates well with most impact categories, such as global warming, resource depletion, acidification […]"; but its use as a stand-alone indicator for the environmental impact of a product is nevertheless limited due to "the large uncertainty in the product-specific fossil CED-based impact scores" resulting from releases and land use due to non-fossil energy consumption [21]. In this study, the non-renewable part of the CED was calculated as described in [22] in order to obtain a value for the "grey energy" of the examined ICT devices.…”
Section: Methodsmentioning
confidence: 99%